The Immune System in Neuroendocrine Tumors - Thiel, A.; Ehlers, M.; Anlauf, M.; Raffel, A.; Stoecklein, N. H.; Schott, M. (Hormone and Metabolic Research, 2011)
During the last 30 years the incidence of neuroendocrine tumors has increased considerably and the overall 5-year survival rate has not changed substantially. Conventional therapeutic approaches appear to show an unsatisfactory effect in the more insidious forms of malignancies. Hence, attempts were made to direct the patient’s own immune system against cancer by vaccinating against different tumor antigens. Up to date, only sporadic achievements were demonstrated in the majority cases of vaccination trials. One of the main hindrances to a successful vaccination comprises tumor-immune-escape mechanisms. This review focuses on the current knowledge concerning tumor immunoevasion strategies and the immune system in neuroendocrine tumors.
Keywords: neuroendocrine malignancies; NET; tumor-immune-escape; immunoevasion